أثر تطبيق حوكمة الشركات على جودة المعلومات المحاسبية - عقاري, مصطفى; بوسلمة, حكيمة (Université de M'sila, 2013)
Nowadays, there is a growing concern about corporate governance due to many reasons, the most important among them, administrative and financial corruption that characterized several big firms; as well as financial crises that affect major economic sectors around the world and which their repercussions are still ongoing up to now. There is, also, some skepticism about a lot of companies seeking to mergers and acquisitions. Several studies and researches have shown that the management of many companies such as (Enron, World Com, ...) used some of the accounting and financial practices in order to hide the facts from stakeholders. Those companies colluded with major audit firms to hide and distort the information associated with the operational performance, funding and investment, causing damage to investors, financial markets and the economies of nations. Therefore, this study aims to clarify the impact of corporate governance on the quality of the accounting information contained in the financial reports. In order to achieve this, we will discuss the concept of corporate governance and its goals, as well as the principles on which it is based. Finally, we will try to highlight how corporate governance can improve the quality of accounting information. This study concluded that the primary motivation for the application of corporate governance is to restore confidence in the accounting information, and that this can only be achieved by: - Ensuring the application of the accounting and auditing standards, - Enhancing the role of the external
Keywords: corporate governance, the quality of accounting information, financial reports